PENGEMBANGAN MODEL TEACHING PERSONALITY AND SOSIAL RESPONBILITY (TPSR) MATA KULIAH PENDIDIKAN JASMANI SEKOLAH DASAR - Fajar Sidik Siregar; Arifin Siregar; Daitin Tarigan (Universitas Negeri Medan, 2022)
Essential investigate targets are: To deliver a item Advancement Demonstrate Educating Identity And Social Duty (TPSR) within the Subject of Physical Instruction in Basic Schools that are substantial. The investigate method employments a 4-D show which is an expansion of Characterize, Plan, Advancement and Spread. The area of the research was carried out within the Essential School Educator Instruction Think about Program, FIP UNIMED. The populace of this investigate is all understudies of the Stambuk Rudimentary School Educator Instruction Consider Program 2020 totaling 225 individuals. The investigate test was arbitrarily doled out to classes, specifically lesson J Customary 2020 totaling 23 understudies. Information collection methods in this think about utilized interviews, surveys and documentation. The comes about of the advancement of the Educating Identity And Social Obligation (TPSR) Show Improvement were gotten (1) The comes about of the fabric master approval as a entire appeared that the Advancement of the Educating Identity And Social Obligation (TPSR) Demonstrate was expressed to be exceptionally substantial (96%) and the comes about of the media master approval as a entire were expressed to be exceptionally substantial (93.3%) (2) The comes about of the adequacy test have an normal esteem of 77,391 with the completeness criteria